Conjuring Planetary Spirits in the Twenty-First Century: Textual-Ritual Entanglements in Contemporary ‘Magic(k)’ - Otto, Bernd-Christian (Entangled Religions, 2023)
This article illustrates textual-ritual entanglements in Western learned magic across almost two millennia through an analysis of Frater Acher’s Arbatel experience. Frater Acher is a contemporary practitioner of ‘magic(k)’ who, between 2010 and 2013, performed a series of conjurations of six planetary spirits inspired by an early modern manual of learned magic named *Arbatel*. Frater Acher combined the Arbatel with ritual techniques from numerous further contexts, among them the late ancient *Greek Magical Papyri*, the Clavicula Salomonis tradition, Paracelsianism, Hermeticism, the Hermetic Order of the Golden Dawn, theurgy, modern imagination techniques, as well as chaos ‘magic(k)’. As a consequence, Frater Acher’s Arbatel experience - as he frames his ritual diaries published online - reveals a strikingly entangled ritual that illustrates the breadth, depth, and complexity of Western learned magic, as well as its manifold entanglements across time and space. His diaries also demonstrate that, even while following largely formalistic premodern scripts of learned magic, contemporary practitioners may nonetheless display a high degree of flexibility, creativity, and innovation. The article closes by reflecting on whether it is likely that such strategies were also present in premodern practitioner scenarios. In doing so, it calls for taking the - extensive but hitherto almost completely neglected - data of experience reports by contemporary practitioners of ‘magic(k)’ into account when interpreting premodern sources of learned magic. As a consequence, this is the first systematic attempt to compare and juxtapose premodern and modern interpretations and mindsets of practitioners of learned magic. It is thus also the first scholarly article that aims at elucidating a premodern manual of learned magic through reading and analysing the experience report of a contemporary practitioner.